Berbagi Isu Aktual dalam Pelaksanaan Undang-Undang Perjanjian Internasional - Purba, Achmad Zen Umar (UI Scholars Hub, 2008)
Despite controversial issue upon the implementation of the Law No. 24 Year 2000 on treaties, the treaty itself was a high achievement in Indonesian national legal system. This article explains certain matters arising in the implementation of treaties in Indonesia. The thoughts were given in a seminar organized by Center for International Law Studies and Ministry of Foreign Affairs overviewed certain affairs regarding implementation of treaties in Indonesia.